ANYONE CAN HEAR: RESEARCH POTENTIAL OF CLASSICAL RADIO FORMAT / У ВСЕХ НА СЛУХУ: АНАЛИТИЧЕСКИЙ ПОТЕНЦИАЛ РАДИО ФОРМАТА CLASSICAL - TSVETKOVSKAYA Tatiana A. / ЦВЕТКОВСКАЯ ТАТЬЯНА АНАТОЛЬЕВНА (Наука телевидения)
The article analyzes the ‘Classical’ format of the radio. For centenary history of the industry’s development, a wealth of factual material has been accumulated and it needs systematization and conceptualization, however classical music is rarely noticed by media researches. The exception is the formative stage of musical broadcasting with organization of the first symphony’s and opera performances’ broadcasting. Meanwhile, there’s a lot of topics, discussion of which can not only interest theorists, but make a significant practical difference. Particular emphasis should be given to the filling of musical air, analyzation of which will help to identify new horizons of applied musicology and to correct radio stations’ strategies. Even though the radio of classical music outlines trends which are specific for academic art in general, there is a number of specialties arising from the nature of mass-media. Duality like this distinguishes the structure of its program too, the quality of which can not be evaluated without taking into account the functional specific of radio. The work of different broadcast’s filling is based on unified principles in accordance with certain set parameters, which helps to choose from basis and form in playlists the compositions of certain styles, genres, characters, duration, connecting them with the elements of sound design and the hosts’ commentaries. Nevertheless, undeniable artistic merit of the content not only ineffective radio of classical music and don’t give them considerable advantages over competitors, but overshadow it to the end of rating. At the same time behind the imaginary easiness of adhering the FM-standards hides the danger of homogenizing the important characteristics of airing compositions, which calls into question the possible realization the humanitarian mission of the classic radio, including the save of cultural heritage, musical education and creative development. In this situation just technology can’t guarantee the result, so it is important to create multi-level approach to the research of radio’s ‘Classical’ format as a original artistic phenomenon and a effective instrument of cultural policy.